OC-115 The use of sofosbuvir based regimens amongst treatment naive and experienced patients with advanced fibrosis/cirrhosis: real world results from a difficult to treat cohort. (22nd June 2015) - Sutherland, D; Forrest, E; Heydtmann, M; Priest, M; Mills, PR; Morris, J; Stanley, A; Fox, R; Barclay, S
Abstract : Introduction: Patients with cirrhosis account for 17–23% of subjects in Phase 3 trials of Sofosbuvir, however strict inclusion/exclusion criteria may make outcomes less reproducible in routine practice. Data is lacking for GT1 treatment experienced (TE) patients, and data for treating GT3 patients with interferon based regimens limited. We sought to establish the tolerability and effectiveness of Sofosbuvir based regimens in such patients with advanced fibrosis/cirrhosis in routine care. Method: We analysed the Scottish HCV Database to identify patients with a liver stiffness measurement (LSM) ≥9.5 kPa, starting a Sof based regimen in Glasgow treatment centres between June and October 2014 inclusive. Data were obtained on demographics, LSM, cirrhosis status, treatment status, baseline labs, Child's score, drug and alcohol use. Data were compared with trial inclusion/exclusion criteria. Baseline viral load, week 4 PCR, EOTR, SVR12 and premature discontinuations were recorded. Results: 123 patients, were treated with either Sof/IFN/Rib (n = 108) or Sof/Rib (n = 15). Baseline characteristics are summarised in Table 1 . 97 (78.9%) patients were cirrhotic (median LSM 20.8 (IQR 14.8–35.5)). The majority were GT3 (68, 55.3%) or GT1 (47, 38.2%). Half (61, 49.6%) were TE, including 9 PI failures. 65 (52.8%) would have failed at least one trial inclusion/exclusion criteria (37 (30.1%) due to baseline labs, 30 (24.4%) recent drug/ alcohol misuse, schizophrenia (1, (0.8%)). At week 4 38/121 (31.4%) patients were undetectable (RealTime HCV, Abbott), 49 (40.5%) detectable <12 IU/ml, and 32 (26.4%) quantifiable (median 23 IU/ml, IQR 15–56). On an ITT basis, 103/114 (90.3%) patients achieved EOTR. 5 discontinued prematurely (including one due to an AE and one death unrelated to treatment), 5 were lost to follow up. 1 patient was detectable (<12 iu/ml) at end of treatment. Per protocol 37/44 (84%) of patients have to date achieved an SVR12. SVR data for the remaining cohort will be presented. Conclusion: Patients with advanced fibrosis/cirrhosis and unfavourable baseline characteristics can be treated effectively with Sofosbuvir based regimens. High rates of detectable HCV RNA at week 4, did not appear to impact on end of treatment response. Initial SVR12 results are encouraging. Disclosure of interest: D. Sutherland: None Declared, E. Forrest: None Declared, M. Heydtmann: None Declared, M. Priest: None Declared, P. Mills: None Declared, J. Morris: None Declared, A. Stanley: None Declared, R. Fox Consultant for: Gilead, Janssen, BMS, Abbvie, Speaker Bureau of: Gilead, Janssen, BMS, Abbvie, S. Barclay Consultant for: Gilead, Janssen, BMS, Abbvie, Speaker Bureau of: Gilead, Janssen.